2021
DOI: 10.1111/inm.12944
|View full text |Cite
|
Sign up to set email alerts
|

Mental health nurses’ disaster nursing competencies: A cross‐sectional study

Abstract: The unprecedented and prolonged coronavirus disease 2019 (COVID‐19) pandemic has escalated the gravity of disasters in the field of mental health. Nurses are health care providers who play a pivotal role in all phases of disaster management and psychiatric nurses are required to be prepared and equipped with competencies to respond to such disasters. This cross‐sectional study aimed to investigate the effects of mental health nurses’ professional quality of life on disaster nursing competencies. This study adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…In this study, rural nurses with prior disaster nursing education showed higher disaster nursing competencies than their counterparts without prior education. These results are consistent with the findings of Jang et al (2022) Discussing the result of the current study on higher disaster nursing competencies among rural nurses with prior education on the related field, prior research shows that, conventionally, the nursing staff pool tends to be smaller in rural than in urban areas, and the same often occurs regarding the difficulty to attract and to retain nurses (Fahs, 2021). Further, efforts to recruit and to retain newly graduated nurses in rural areas have generally emphasized nursing managerial support and situational learning as advantages (Lea & Cruickshank, 2017).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In this study, rural nurses with prior disaster nursing education showed higher disaster nursing competencies than their counterparts without prior education. These results are consistent with the findings of Jang et al (2022) Discussing the result of the current study on higher disaster nursing competencies among rural nurses with prior education on the related field, prior research shows that, conventionally, the nursing staff pool tends to be smaller in rural than in urban areas, and the same often occurs regarding the difficulty to attract and to retain nurses (Fahs, 2021). Further, efforts to recruit and to retain newly graduated nurses in rural areas have generally emphasized nursing managerial support and situational learning as advantages (Lea & Cruickshank, 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Ohta et al (2020) Furthermore, prior participation in disaster nursing care was a predictor of rural nurses' disaster nursing competencies in our sample. On this topic, the literature shows that nurses who participated in disaster nursing demonstrated higher confidence levels in emergency nursing (Tzeng et al, 2016) and higher disaster nursing competencies (Jang et al, 2022;Labrague et al, 2016) than those without such experience. Moreover, nurses with rich clinical experience are more willing to participate in disaster nursing (Sonneborn et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During this treatment period, nurses and healthcare providers play a key role in all stages of disaster management. Nurses need to be prepared and capable of responding to such disasters [ 7 ]. Unmet care needs and poor quality of care for this resident population have been widely reported [ 1 ].…”
Section: Discussionmentioning
confidence: 99%